Cultural differences in wine conceptualization among consumers in France, Portugal and South Africa - (:unkn) unknown (My University, 2024)
Consumers’ mental pictures of wine are multifaceted and are shaped by their sensory (taste, smell, visual, sensation) perceptions, in addition to emotional, cultural and extrinsic (brand, price, and awards) influences. This study explores whether consumers from three different wine cultures share mental representations of three wine concepts. Through an online survey, French, Portuguese, and South African wine consumers described their conceptualizations of Wine, Red wine and White wine aroma. Given these nations’ rich winemaking traditions and diverse wine styles, differences in consumer perspectives were likely to emerge. The findings demonstrate that, regardless of cultural background, the broad concept of Wine aligns with the more specific Red and White wine conceptualizations, although the latter concepts diverge from each other. Notably, cultural contexts significantly influence participants’ representations of Red Wine , with particularly marked contrasts between the South African and French respondents. This suggests that like experts, wine consumers have also built representations of wine through semantic memory. This cross-cultural analysis of consumer interpretations of wine concepts holds the potential for refining marketing strategies to overcome cultural barriers in wine purchasing behaviour.
Keywords: African Research